Demodulation and de-multiplexing of a fibre Bragg grating sensor array using volume holograms - Reeves, Richard John (Cranfield University, 2009)
The demodulation of a Wavelength Division Multiplexed FBG sensor array by a matching array of holograms hosted within a Volume Holographic (VH) material is considered within this thesis. The FBG sensor elements possess separate quiescent wavelengths and operate within different wavelength ranges. The edge of the transfer function of the demodulating holographic element is aligned with the operating range of the matching sensor element. The holographic element then diffracts a fraction of the sensor signal depending on its instantaneous wavelength. The signals from each of the sensor elements are also diffracted through separate angles to matching detectors so de-multiplexing the sensor array. A scheme using narrow bandwidth holographic transfer functions to demodulate a two element strain sensor array fabricated 4nm apart is reported. The transfer functions and the hysteresis within the PZT actuator, applying the strain, are represented mathematically and used to process results. These are compared with a normalised saw-tooth voltage waveform applied to the PZT to achieve a high Pearson correlation factor of 0.9992. The holograms however possessed poor diffraction efficiency <1% so severely degrading strain resolution. The crosstalk between the sensors’ channels is measured as -8.3dB. The demodulation scheme is intensity based so is susceptible to fluctuations in source intensity and fibre bend losses. An intensity reference scheme is therefore demonstrated using two holograms to demodulate a single FBG strain sensor. The sensor’s signal is divided by the two holograms and the intensity of the respective parts recorded on matched photo-detectors. Ratiometric detection is then used to identify changes in applied strain while disregarding fluctuations in source intensity and fibre bend losses. The standard difference over sum equation for ratiometric detection however is modified to take account of the respective holographic transfer functions.